TIL KONSULTATION HOS ÅNDERNE: Om klarsyn, energier og magi i Danmark - Steffen, Vibeke (Tidsskriftet Antropologi, 2010)
There is a long-standing anthropological tradition of studies where the concept of magic is related to crisis and the re-establishment of order, whether on a social or an individual level. The risk of this approach, however, is that we may mistake the intention with magic for its result, and thus overestimate the role of crisis, the management of problems and the construction of meaning. This article demonstrates that instead of providing answers and solutions, the engagement with magic may just as well open up for new questions and new problems. The subject of the study is spiritualism and second sight as practised in contemporary Danish society primarily by women. In this context, magic is not necessarily something extraordinary that people turn to when facing severe trouble, but rather a way of dealing with social relations in everyday life. My approach is inspired by Evans- Pritchard’s classic work on witchcraft, oracles and magic among the Azande in the sense that the concept of magic forms only one leg in a triangle with energies and second sight as the other two. Second sight is provided by mediums passing on messages from deceased relatives or other spirits at platform demonstrations or in private consultations. The messages often deal with distance and proximity in social relations and how to protect yourself against feelings of being drained of energy or invaded by other human or spiritual beings. The term energy provides a sense of physical reality to these otherwise subtle feelings and makes it possible to deal with them in concrete situations through spells, invocations, and other kinds of magic manipulation. Keywords: Spiritism, social relations, the boundaries of self , women.